Ginseng and Polygonum multiflorum formula protects brain function in Alzheimer’s disease - Liu, Jing-Jing; Wei, Feng; Wang, Ya-Dan; Liu, Jing; Xu, Bei-Lei; Ma, Shuang-Cheng; Yang, Jian-Bo (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease (AD) is a progressive neurodegenerative disorder with no effective treatment currently available. The Panax ginseng C.A.Mey. and Polygonum multiflorum Thunb. formula (GSPM) has shown potential neuroprotective effects, but its therapeutic efficacy and underlying mechanisms in AD remain unclear and require further investigation.MethodsIn this study, senescence-accelerated mouse prone 8 (SAMP8) mice, an AD model, were treated with GSPM (low: 117 mg/kg, high: 234 mg/kg) or donepezil (1.3 mg/kg) via gavage for 2 months. Cognitive function was assessed using the Morris water maze. Hippocampal morphology was evaluated by H&E staining, and neuronal apoptosis was detected by TUNEL assay. Microgliosis and astrogliosis were analyzed by Iba1 and GFAP immunohistochemistry. Levels of phosphorylated Tau, Aβ1-42, Aβ1-40, inflammatory cytokines, oxidative stress markers, and senescence markers were measured. Gut microbiota composition was analyzed by 16S rRNA sequencing. In vitro, the effects of GSPM were evaluated in Aβ1-42-stimulated HT22 hippocampal neurons. Cell viability was assessed via CCK-8, and apoptosis was detected by flow cytometry. The AMPK/Sirt1 pathway was investigated by Western blotting, and SIRT1-dependent effects were evaluated following EX527 treatment, a SIRT1 inhibitor.ResultsGSPM treatment improved cognitive function, reduced hippocampal tissue damage, and decreased neuronal apoptosis in AD mice. It alleviated neuroinflammation by reducing microgliosis and astrogliosis and lowered the levels of p-Tau protein and Aβ accumulation in both the hippocampus and cerebrospinal fluid. Additionally, GSPM reversed the enhanced inflammation, oxidative stress, and neuronal senescence observed in AD mice. Furthermore, GSPM modulated gut microbiota composition by reducing microbial diversity and restoring the Firmicutes/Bacteroidetes ratio to levels similar to those in control mice. GSPM increased the abundance of Lactobacillus, which was negatively correlated with inflammation, Aβ1-42, p-Tau, and senescence markers. It also decreased the abundance of bacteria, such as Oscillibacter, Helicobacter, and Odoribacter, which are associated with inflammation, oxidative stress, and neuronal senescence. In line with in vivo findings, GSPM increased cell viability, reduced apoptosis, and alleviated oxidative stress in Aβ1-42-stimulated HT22 hippocampal neurons. It also decreased the production of pro-inflammatory cytokines and reduced expression of senescence markers in vitro. Furthermore, GSPM restored AMPK phosphorylation and Sirt1 expression in neurons. Notably, inhibition of Sirt1 by EX527 reversed the neuroprotective effects of GSPM.ConclusionOur data demonstrated that GSPM exhibits protective effects on AD via suppressing the inflammation, oxidation, and senescence, possibly through regulating the Sirt1 signaling. These findings provided a novel therapeutic approach for AD.